2017
DOI: 10.1017/s0007114517000393
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry and cranberry polyphenols improve insulin sensitivity in insulin-resistant, non-diabetic adults: a parallel, double-blind, controlled and randomised clinical trial

Abstract: Plant-derived foods rich in polyphenols are associated with several cardiometabolic health benefits, such as reduced postprandial hyperglycaemia. However, their impact on whole-body insulin sensitivity using the hyperinsulinaemic-euglycaemic clamp technique remains under-studied. We aimed to determine the effects of strawberry and cranberry polyphenols (SCP) on insulin sensitivity, glucose tolerance, insulin secretion, lipid profile, inflammation and oxidative stress markers in free-living insulin-resistant ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 55 publications
2
110
0
4
Order By: Relevance
“…In the study performed by Stull et al (18) , a 6-week intake of a smoothie with 45 g of blueberry extract powder increased insulin sensitivity by 22 %. As recently reported by Paquette et al (21) , intake of 1•84 g daily of a strawberry-cranberry powder blend for 6 weeks resulted in a lower first-phase insulin secretion response as measured by C-peptide levels during the first 30 min of the OGTT. In our study, we examined whether a cranberry beverage could improve insulin resistance, which is a risk factor for the development of diabetes.…”
Section: Discussionsupporting
confidence: 65%
“…In the study performed by Stull et al (18) , a 6-week intake of a smoothie with 45 g of blueberry extract powder increased insulin sensitivity by 22 %. As recently reported by Paquette et al (21) , intake of 1•84 g daily of a strawberry-cranberry powder blend for 6 weeks resulted in a lower first-phase insulin secretion response as measured by C-peptide levels during the first 30 min of the OGTT. In our study, we examined whether a cranberry beverage could improve insulin resistance, which is a risk factor for the development of diabetes.…”
Section: Discussionsupporting
confidence: 65%
“…Clinical studies using strawberries showed reduced insulin needs for managing postprandial glycemia, independent of fiber content (13). Two other trials have reported improved insulin sensitivity accessed by hyperinsulinemic-euglycemic clamp after 6 weeks of consumption of polyphenols from blueberry (28) or an extract blend of strawberry and cranberry (29). The data from the present study with red raspberries suggest improved insulin action in peripheral tissues aiding in postmeal glycemic control and apparently lasting effects over the 24-hour period, warranting follow-up in a chronic feeding design.…”
Section: Discussionmentioning
confidence: 99%
“…The main human-interventional studies with cranberry or cranberry products considering glycemic metabolism are listed in Table 2. In sum, although nutritional intervention studies with cranberries on glucose metabolism are still scarce, some of them have shown that cranberry products may promote glucose homeostasis by reducing fasting glycemia, improving HOMA-IR, increasing insulin sensitivity, and preventing compensatory insulin secretion [44,46,47], whereas others did not demonstrate any significant change on this feature [16,48]. From these studies, it is still not possible to define if duration and consumed amount of cranberry are responsible for these controversial results.…”
Section: Cranberry and Glucose Metabolismmentioning
confidence: 99%
“…Paquette et al [47] A parallel, double-blind, controlled, and randomized clinical trial to determine the effects of strawberry and cranberry polyphenols (SCP) on insulin sensitivity, glucose tolerance, insulin secretion, lipid profile, inflammation, and oxidative stress markers in free-living insulin-resistant overweight or obese human subjects.…”
Section: Cranberry and Blood Pressurementioning
confidence: 99%